Isotherm, kinetics and thermodynamic studies of Cd 2+ adsorption from aqueous solution onto cellulose nanocrystals obtained from cassava peel - C. V. Abiaziem; C. T. Onwordi; L. F. Petrik; A. B. Williams (Songklanakarin Journal of Science and Technology (SJST), 2021)
Cd2+ adsorption from aqueous solution onto cellulose nanocrystals from cassava peel (CP) was successfully studied. The sample was acid hydrolysed into cellulose nanocrystals using 64% sulphuric acid at 45oC for 45 min and was used as an adsorbent for the removal of Cd2+ from aqueous solution. Cellulose nanocrystals were characterised using high-resolution scanning electron microscope (HR-SEM), x-ray diffraction (XRD), and thermogravimetric analysis (TGA). The different optimization factors were studied. The adsorption equilibrium data were best fit by the Freundlich model with an R2 of 1, indicating good surface heterogeneity of the active sites. Kinetic data were best fit by the pseudo-second order model type. The thermodynamic parameters enthalpy, entropy, and the negative change in Gibbs free energy, imply that the adsorption of Cd2+ onto CPCNC was exothermic, spontaneous, and feasible. This nanomaterial has good potential for use in successful removal of Cd2+ from wastewaters.